International journal of food contamination (BioMed Central Ltd., part of Springer Nature, 2014)
The International Journal of Food Contamination publishes baseline, monitoring data, indicating the qualitative and quantitative presence of microbiological and chemical contaminants in foods, animal feed, and their raw materials.
Keywords: Food contamination : Periodicals; Food : Microbiology : Periodicals; Food Contamination; Food Microbiology; Food contamination; Food : Microbiology; Diet & Clinical Nutrition